Motivasi dan Minat Belajar PAK Terhadap Moral dan Perkembangan Etika Siswa (Kajian Amsal 1:1-7) - Sihotang, Siska; Bilo, Dyulius Thomas; Ginting, Saronisa (Jurnal Teologi dan Pendidikan Kristen, 2023)
Christian Religious Education (CE) has a vital role in shaping students' moral and ethical development. This study aims to analyze the study of Proverbs 1:1-7 on students' learning motivation and interest in learning, as well as its impact on their moral and ethical development. This study used a qualitative approach by involving participants consisting of students in high school who received CE. Data were collected through in-depth interviews, observation, and analysis of documents, then presentation of data before concluding. The results showed that Proverbs 1:1-7 contributed positively to students' learning motivation. The material presented in the study provides a deep understanding of moral and ethical values in Christian teachings. This increases students' interest in learning because it sees the direct relevance between religious education and daily life. In addition, this study also has a significant impact on the moral and ethical development of students. Students develop a better understanding of the importance of integrity, honesty, and respect for others. This research has important implications for religious education practitioners and relevant stakeholders to consider the use of materials in curriculum and learning activities to improve the moral and ethical development of students.